The correct answer is (b) 0
The best I can explain: Put x =r.cos(ϴ) : y = r.sin(ϴ)
=\(lt_{(x,y)\rightarrow (0,0)}\frac{(r^7.sin^7(\theta))(r^{98}.sin^{98}(\theta))-(r^{97}.cos^{97}(\theta))(r^8.sin^8(\theta))+(r^{105}.cos^{105}(\theta))}{(r.cos(\theta)(r^7.sin^7(\theta))+(r^8.cos(\theta))}\)
=\(lt_{(x,y)\rightarrow (0,0)}\frac{r^{105}}{r^8}\times \frac{(sin^7(\theta))(sin^{98}(\theta))-(cos^{97}(\theta))(sin^8(\theta))+(cos^{105}(\theta))}{(cos(\theta)(sin^7(\theta))+(cos(\theta))}\)
=\(lt_{(x,y)\rightarrow (0,0)}(r^{97})\times \frac{(sin^7(\theta))(sin^{98}(\theta))-(cos^{97}(\theta))(sin^8(\theta))+(cos^{105}(\theta))}{(cos(\theta)(sin^7(\theta))+(cos(\theta))}\)
= 0